Hubungan antara Persepsi Siswa tentang Kompetensi Pedagogik Guru dengan Hasil Belajar Siswa Kelas VII pada Mata Pelajaran IPS di SMP Ma’arif NU 01 Pekuncen, Banyumas Tahun Pelajaran 2018/2019 - Purnomo, Arif; Nisa, Aisyah Nur Sayidatun; Purwandari, Purwandari (Universitas Negeri Semarang, 2020)
The competency possessed by the teacher affects the attention of students in participating in the learning process which will produce student learning outcomes. This type of research used in this research is quantitative research. The results of this study are the relationship between students' perceptions of teacher pedagogical competence with the learning outcomes of seventh-grade students of social studies at SM Ma'arif NU 01 Pekuncen, Banyumas Regency, Academic Year 218/2019 there is a positive and significant relationship between the two variables. This is evidenced by the obtained correlation value of the two variables is 0.943 with a significance of 0.000 and the student's perception variable about teacher pedagogical competence is related to the learning outcome variable by 88.9%.